Common Data Elements in the Assessment of Military-Related PTSD Research Applied in the Consortium to Alleviate PTSD. Issue 5 (25th September 2018) - Ben Barnes, J; Presseau, Candice; Jordan, Alexander H; Kline, Nora K; Young-McCaughan, Stacey; Keane, Terence M; Peterson, Alan L; Litz, Brett T
Abstract: Introduction: Driven by the need to share data, sufficiently power studies, and allow for cross-study comparisons of medical and psychiatric diseases, the President's National Research Action Plan issued in 2013 called for the use of state-of-the-art common data elements (CDEs) for research studies. CDEs are variables measured across independent studies that facilitate methodologically sound data aggregation and study replication. Researchers in the field of military-related post-traumatic stress disorder (PTSD) have suggested applicable CDEs; however, to date, these recommendations have been conceptual and not field-tested. The Consortium to Alleviate PTSD (CAP) – an interdisciplinary and multi-institutional, military-related PTSD research consortium funded by the Departments of Defense and Veterans Affairs – generated and applied CDEs that can be used to combine data from disparate studies to improve the methodological and statistical capabilities of study findings. We provide a description and rationale for the CAP CDEs and details about administration with two main goals: (1) to encourage military-related PTSD researchers to use these measures in future studies and (2) to facilitate comparison, replication, and data aggregation. Materials and Methods: The CAP compiled mandated (core) and optional CDEs based on the following criteria: (1) construct applicability to military-related PTSD; (2) precedence (use) in prior, related research; (3) published and strong psychometric evidence; (4) no cost (public domain); and (5) brevity, to limit participant burden. We provided descriptive statistics and internal consistency reliabilities for mandated measures from an initial cohort of around 400 participants enrolled in CAP studies. Results: Mandated CDEs in the CAP were found to have very good internal consistency reliability. Conclusion: Although further research is needed to determine the incremental validity of these CDEs, preliminary analyses indicated that each mandated measure has very good internal consistency reliability. Investigators designing military-related PTSD research should consider using these field-tested CDEs to facilitate future data aggregation. Feedback based on empirical evidence or practical concerns to improve these CDEs is welcome.